Tipologi Kitab Al-Ma'ajim dalam Kodifikasi Hadis (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2016)
The method which is used by theologian in hadi>th codification has a trend that change from time to time. After third century of hijriyah, some theologians arrange hadith’s book using the method that has already taught to them before, but others have a different method. One of the method which is dissimilar from others is hadith codification method or it is called Mu‘jam. Mu‘jam is a hadi>th codification typology that is based on the friend of the Prophet’s musnad or the writer’s teacher that is arranged based on alphabet. In some sample, it is seemed that Mu‘jam’s book also shows some friends of the Prophet’s biography before showing the history of them. Mu‘jam’s book is classified into two groups. They are Mu‘jam al-Shuyukh (based on teacher’s names) and Mu‘jam al-Sahabah (based on friends of the Prophet’s names). Commonly, there are some quality of hadith s in Mu‘jam’s books. There are sahih, hasan, da‘if even mawdu’ (false). One of the benefit in Ma‘ajim’s book is as the main reference of Prophet’s musnad hadith. It means continued until the Prophet himself and containing lots of hadith that is not found in al-Kutub al-Sittah. Moreover, Mu‘jam’s book is one of the main references to know the biography of Sahabat (friend’s Prophet), nasab (offspring), and their virtue.